2017
DOI: 10.1016/j.jalz.2017.06.2265
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hypoperfusion is not associated with an increase in amyloid β pathology in middle‐aged or elderly people

Abstract: IntroductionIt is hypothesized that cerebral hypoperfusion promotes the development of Alzheimer pathology. We therefore studied whether longstanding cerebral hypoperfusion is associated with Alzheimer pathology in nondemented humans.MethodsCerebral blood flow and amyloid β (18F-Flutemetamol) positron emission tomography retention were assessed in eleven patients with unilateral occlusion of precerebral arteries resulting in chronic and uneven hypoperfusion. A subset of patients underwent tau (18F-AV-1451) pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…In our study, neither IMT nor carotid plaques were significantly associated with AD pathology measured as abnormal CSF Aβ 42 and CSF Aβ 42 /p‐tau ratio in a cognitively unimpaired subcohort (n = 330). This finding is in line with a previous cross‐sectional study on IMT and Aβ PET and a small study of participants with unilaterally occluded carotid arteries, where no association between hypoperfusion and Aβ or tau accumulation was found . Our results may be interpreted as being suggestive of an association between higher IMT and abnormal AD biomarkers (OR = 1.28 and 1.35; see Table ) although encompassing statistical uncertainty because the CIs overlap 1, which may be due to the relatively small sample size yielding large CIs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, neither IMT nor carotid plaques were significantly associated with AD pathology measured as abnormal CSF Aβ 42 and CSF Aβ 42 /p‐tau ratio in a cognitively unimpaired subcohort (n = 330). This finding is in line with a previous cross‐sectional study on IMT and Aβ PET and a small study of participants with unilaterally occluded carotid arteries, where no association between hypoperfusion and Aβ or tau accumulation was found . Our results may be interpreted as being suggestive of an association between higher IMT and abnormal AD biomarkers (OR = 1.28 and 1.35; see Table ) although encompassing statistical uncertainty because the CIs overlap 1, which may be due to the relatively small sample size yielding large CIs.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with a previous cross-sectional study on IMT and Aβ PET 15 and a small study of participants with unilaterally occluded carotid arteries, where no association between hypoperfusion and Aβ or tau accumulation was found. 30 Our results may be interpreted as being suggestive of an association between higher IMT and abnormal AD biomarkers (OR = 1.28 and 1.35; see Table 3) although encompassing statistical uncertainty because the CIs overlap 1, which may be due to the relatively small sample size yielding large CIs. Indeed, some neuropathological 31 and experimental 32 studies suggest a link between intracerebral atherosclerosis and Aβ pathology, possibly mediated by hypoxia leading to increased Aβ cleavage and accumulation via enzymatic upregulation as well as by vascular narrowing leading to reduced Aβ clearance.…”
Section: Discussionmentioning
confidence: 67%
“…CBVD can lead to cerebral hypoperfusion that could result in degradation of the neurovascular unit and subsequent deposition of beta-amyloid and tau, eventually leading to dementia (this vascular pathway has been the focus of several literature reviews [7072]). The relationship between cerebral blood flow and ADNP remains inconclusive, given a recent study that found no association between cerebral blood flow and cortical uptake of amyloid (flutemetamol) or tau (AV-1451) tracers on PET imaging in 11 middle-aged to elderly patients with unilateral occlusion of precerebral arteries [73]. …”
Section: Discussionmentioning
confidence: 99%
“…A study with 130 samples suggested a negative correlation between CIMT and the MMSE score (Zhou et al, 2016). On the other hand, some researchers found no significant association between the severity of stenosis of carotid and intracranial arteries and cognitive impairment (Lopez‐Oloriz et al, 2013), and decreased brain blood flow caused by atherosclerosis might not lead to increased deposition of Aβ and hyperphosphorylation of tau protein (Hansson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%